The passage of Australia’s data retention regime: national security, human rights, and media scrutiny - Nicolas Suzor; Kylie Pappalardo; Natalie McIntosh (Internet Policy Review)
In 2015, the Australian government passed the Telecommunications (Interception and Access) Amendment (Data Retention) Act, which requires ISPs to collect metadata about their users and store this metadata for two years. From its conception, Australia’s data retention scheme has been controversial. In this article we examine how public interest concerns were addressed in Australian news media during the Act’s passage. The Act was ultimately passed with bipartisan support, despite serious deficiencies. We show how the Act’s complexity seemed to limit engaged critique in the mainstream media and how fears over terrorist attacks were exploited to secure the Act’s passage through parliament.